4‐Aryl‐4H‐Chromene‐3‐Carbonitrile Derivates: Synthesis and Preliminary Anti‐Breast Cancer Studies. (3rd July 2015) - Thomas, Nancy; Zachariah, Subin Mary; Ramani, Prasanna
Abstract : A series of new 4‐aryl‐4 H ‐chromene‐3‐carbonitrile derivatives were obtained byone‐pot synthesis using substituted benzaldehydes, malononitrile, and substituted phenols. All the synthesized compounds (1a, 1b, 1c, 1d, 1e ) were screened in vitro for antioxidant and anticancer activities. Compounds1c, 1d, 1e showed significant antioxidant activity in nitric oxide free radical scavenging method while compounds1c and1e showed significant activity inhydrogen peroxide free radical scavenging method. The other compounds showed significant to moderate activities in both the methods in comparison with ascorbic acid and butylated hydroxytoluene as standards. Compounds1c, 1d, 1e exhibited good anticancer activity, using Michigan Cancer Foundation‐7 (MCF‐7) cell line, compared with those of other synthesized compounds. Abstract :